The Effect of Discovery Learning Model Assisted by Liveworksheet on Biology Learning Independence of Class XI SMA - Ika Sri Wahyuni; Arsad Bahri; Muhiddin Palennari (Quagga: Jurnal Pendidikan dan Biologi, 2024)
This research is a quasi-experimental research that aims to determine the effect of discovery learning model assisted by liveworksheets on the independence of biology learning of high school class XI students. The population in this study were all students of class XI MIPA SMAN 14 Makassar. The research sample was selected randomly (random sampling) so that two classes were obtained, namely class XI MIPA 6 as an experimental class that used the discovery learning model assisted by liveworksheets and class XI MIPA 1 as a control class with 33 students each. Data collection was carried out by giving a questionnaire of learning independence as many as 30 statement items with four answer choices. Data were analyzed by descriptive statistics and inferential statistics. The results of descriptive statistical analysis showed that the average value of the posttest in the experimental class was 86.09 higher than the average value of the control posttest which was 73.48. This study used covariate analysis (Anacova). Based on the results of inferential analysis obtained sig 0.001 smaller than 0.05. It can be concluded that the discovery learning model assisted by liveworksheets has an effect on the learning independence of biology students in class XI SMA.